2009
DOI: 10.1152/jn.90566.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabotropic Glutamate Receptor Expression and Modulation in Two Neocortical Inhibitory Networks

Abstract: . Differential metabotropic glutamate receptor expression and modulation in two neocortical inhibitory networks. J Neurophysiol 101: 2679 -2692, 2009. First published February 25, 2009 doi:10.1152/jn.90566.2008. Taking advantage of transgenic mice with genetically labeled GABAreleasing interneurons, we examined the cell-specific patterns of mGluR expression in two broadly defined subtypes of inhibitory interneurons in layer IV of somatosensory cortex. Electrophysiological recording combined with application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…Metabotropic glutamate receptor mGluR2-selective agonists selectively activate fast-spiking interneurons in the cortex (Sun et al, 2009) and have an antipsychotic action (Marek et al, 2010). The expression of kainate receptor subunit GluR5 (not GluR6) mRNA was reduced in cortical interneurons of schizophrenics (Woo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Metabotropic glutamate receptor mGluR2-selective agonists selectively activate fast-spiking interneurons in the cortex (Sun et al, 2009) and have an antipsychotic action (Marek et al, 2010). The expression of kainate receptor subunit GluR5 (not GluR6) mRNA was reduced in cortical interneurons of schizophrenics (Woo et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the suppression of inhibition is proposed as a potential contributor to the enhanced mGluR-dependent synaptic plasticity previously observed in the Fmr1 KO hippocampus [Huber et al, 2002] and cognitive impairment in FXS. This finding not only suggests a link between excessive group I mGluR signaling and hyperplasticity of excitatory synapses in FXS, but also between mGluRs and alterations in inhibitory function, an important consideration, given that group I mGluRs are differentially expressed in a number of inhibitory neuron subtypes [Kerner et al, 1997;Stinehelfer et al, 2000;Sun et al, 2009]. Interestingly, excessive group I mGluR-eCB-dependent suppression of inhibition has also been observed in the striatum [Maccarrone et al, 2010], indicating that disruption of this signaling pathway may be disrupting inhibitory transmission in other brain regions as well.…”
Section: Crucial Gabaergic Synapse Components Are Dysregulated In Fxsmentioning
confidence: 94%
“…mGluR1 can activate glutamatedriven synaptic inhibition in the cerebellum (Karakossian and Otis 2004). A recent study from our laboratory (Sun and Neugebauer 2011) showed that mGluR1 also activates feedforward inhibition of mPFC pyramidal cells. mGluR1 and mGluR5 subtypes are expressed in the PFC (Cauli et al 2000;Muly et al 2003).…”
Section: Ji G Neugebauer Vmentioning
confidence: 98%